The effects of congested fixtures period on tactical and physical performance in elite football - Folgado, H.; Duarte, R.; Marques, P.; Sampaio, J. (Journal of Sports Sciences, 2015)
The aim of this study was to examine the physical and tactical performances of a professional football team under congested and non-congested fixture periods. Six home matches of an English professional football team were analysed during competitive season (3 matches distancing three days from the previous fixture and 3 matches distancing six or more days from the previous fixture). Players` physical performances were measured by the total distance covered and distance covered at different speed categories. Tactical performances were measured by the percentage of time of players` movement synchronisation of lateral and longitudinal displacements. This variable was calculated considering all the possible pairs of outfield players, for the overall match and at different speed categories. Results showed no differences in the physical performance, although players` spent more time synchronised during the non-congested fixtures compared to congested fixtures, both for lateral (41.26% to 38.51%, ES: -0.3, P < 0.001) and longitudinal displacements (77.22% to 74.48%, ES: -0.5, P < 0.001). These coordination differences were particularly evident at the lower speed categories and in dyads composed by positions that tend to be further apart during the match, typically central and wing positioned players. Tactical performance seems to be affected by fixtures distribution, with players` spending more time synchronised during the non-congested fixtures. As players` cover the same amount of distance at similar intensities in both fixtures distribution, this reduction of synchronisation may be associated with an increased perception of fatigue and consequent adaptation strategies.